Research of cement stone degradability in difficult mining and geological conditions of Ukraine - Stavychnyi, Ye.M.; Femiak, Ya.M.; Vytyaz, O.Yu.; Tershak, B.A.; Klymyuk, M.M.; Kindrat, V.V. (Physics and Chemistry of Solid State, 2024)
The features and prospects of hydrocarbon potential of Ukraine are analyzed. It is established that the basic resource of oil and gas deposits is concentrated in difficult mining and geological conditions. The formulations of basic plugging materials were researched and their sedimentation stability destruction was established. The influence of technological processes during well completion on the casing and cementing system is assessed and the impact of these operations on the state of the insulating ring in the well is characterized. The degradability of cement stone based on base cements PCT I-100 was assessed by visual research and X-ray phase analysis (XPA). The deformation of stone samples under the influence of an aggressive medium and the almost complete absence of binding crystalline hydrates in the samples at XPA were established. The results obtained indicate the need to use degradation-resistant plugging materials. The advantages of plugging systems based on composite cements are characterized and typical modifiers that can be used to regulate the properties of plugging mud and cement stone are presented. The influence of an aggressive environment on cement stone based on composite material DRCT was researched. Quantitative analysis of the elemental composition and XPA of the researched samples of DRCT cement stone in aggressive mediums of magnesium chloride and sulfuric acid confirms the corrosion resistance of the stone made of material DRCT. The research results allow us to recommend the cementing material DRCT for cementing oil and gas wells in difficult mining and geological conditions.